2014
DOI: 10.1380/ejssnt.2014.79
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study for Crystal Structure Deformation in A<sup><i>N</i></sup>B<sup>8</sup><sup>-</sup><sup><i>N</i></sup> Compounds

Abstract: The crystal-structure deformation depending on lattice parameters in A N B 8−N compounds is investigated on the basis of density-functional theory (DFT) calculations. Our DFT calculations for C, BN and BeO demonstrate that the energy difference in cohesive energy along crystal structure deformation path strongly depends on the ionicity fi of materials. In particular, the energy barriers for structural deformation from threefold coordinated (hexagonal graphite) to fourfold coordinated (wurtzite) structures in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…17) The valence electrons are expanded by the plane-wave basis set with a cutoff energy of 49 Ry that gives sufficient convergence of cohesive energies. Table I shows the cohesive energy (D e ) and equilibrium interatomic distance (r e ) values with experimental values of r e at Z = 4 for BN, [18][19][20] AlN, GaN, and InN 19,21,22) used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…17) The valence electrons are expanded by the plane-wave basis set with a cutoff energy of 49 Ry that gives sufficient convergence of cohesive energies. Table I shows the cohesive energy (D e ) and equilibrium interatomic distance (r e ) values with experimental values of r e at Z = 4 for BN, [18][19][20] AlN, GaN, and InN 19,21,22) used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Although the relative stability among various structures including Hex, WZ, zinc blende (ZB), and rocksalt (RS) structures in group‐III nitrides has been clarified, the crystal structure transformation among various structures still remains unclear. In our previous study, we have investigated the crystal structure deformation and its energy barrier in C, BN, and BeO . It has been found that the structural transformation originates from the ionicity of materials.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we have investigated the crystal structure deformation and its energy barrier in C, BN, and BeO. [10] It has been found that the structural transformation originates from the ionicity of materials. In this study, we extend our study to investigate the crystal structure deformation among Hex, WZ, and RS structures in group-III nitrides (BN, AlN, GaN, and InN) by using density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…1 where the cohesive energies from G to RS via WZ can be continuously obtained by varying axial ratios b/a and c/a with incorporating atomic volume change and atomic displacements in the unit cell. 16) We use the generalized gradient approximation (GGA) 17) and the normconserving pseudopotentials. 18) The valence electrons are expanded by the plane-wave basis set with a cutoff energy of 49 Ry that gives enough convergence of cohesive energies.…”
mentioning
confidence: 99%